Healthy Eating: Cooking for One - Emily Minton (EDIS)
You may think that cooking for one is a difficult task because most recipes are intended to serve four or more people. However, there are things you can do to make cooking for one easy and enjoyable. This 2-page fact sheet includes a table of measurements for reducing recipes. Written by Emily Minton and published by the UF Department of Family, Youth and Community Sciences, May 2012.